Achieving Social and Ecological Outcomes in Collaborative Environmental Governance: Good Examples from Swedish Moose Management - Sabrina Dressel; Annelie Sjölander-Lindqvist; Maria Johansson; Göran Ericsson; Camilla Sandström
Collaborative governance approaches have been suggested as strategies to handle wicked environmental problems. Evaluations have found promising examples of effective natural resource governance, but also highlighted the importance of social-ecological context and institutional design. The aim of this study was to identify factors that contribute to the achievement of social and ecological sustainability within Swedish moose ( Alces alces ) management. In 2012, a multi-level collaborative governance regime was implemented to decrease conflicts among stakeholders. We carried out semi-structured interviews with six ‘good examples’ (i.e., Moose Management Groups that showed positive social and ecological outcomes). We found that ‘good examples’ collectively identified existing knowledge gaps and management challenges and used their discretionary power to develop procedural arrangements that are adapted to the social-ecological context, their theory of change, and attributes of local actors. This contributed to the creation of bridging social capital and principled engagement across governance levels. Thus, our results indicate the existence of higher-order social learning as well as a positive feedback from within-level collaboration dynamics to between-level collaboration. Furthermore, our study illustrates the importance of institutional flexibility to utilize the existing knowledge across stakeholder groups and to allow for adaptations based on the social learning process. adaptive management; collaborative governance regime; collaboration dynamics; institutional flexibility; leadership; multi-level governance; social capital; social learning